MENULIS PUISI DENGAN TEKNIK PEMBELAJARAN YANG KREATIF - Dina Merdeka Citraningrum* (Belajar Bahasa, 2016)
Learning to write poetry is still experiencingnumbers of  obstacles. The obstacles are both from students and teachers. Students tend to prefer popular science essay writing than poetry writing. It sometimes becomes the most difficult thing for students to do. This is due to the students thought that the poem is toocomplicated in terms of language and interpretation. In addition, the un-achieved learning goals performed by the teacher becomes an obstacle in poetry writing class. Therefore, teachers should start looking for ways to make students eager to learn to write poetry. Teachers must provide effective and creative learning techniques to students at school. The understanding that writing poetry can be learned must be imparted to the students so that they would be open-minded to learn to write poetry.Key words: Writing Poetry, Learning Techniques.